2006
DOI: 10.1111/j.1944-9720.2006.tb02895.x
|View full text |Cite
|
Sign up to set email alerts
|

Current Perceptions and Beliefs Among Incoming College Students Towards Foreign Language Study and Language Requirements

Abstract: Opinions of foreign language study, as well as attitudes toward specifi c cultures and languages, infl uence student motivation and success. The purpose of the present study is to catalogue and report the perceptions and attitudes of recent incoming college students (freshman and transfer students) concerning foreign or second language (L2) study and foreign language requirements in a post-9/11 context. The results offer insights into students' evolving beliefs and concerns, which can be used to informand subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…However, available research on reasons learners study languages might lead to certain speculations. Recalling Roberts's () findings, Price and Gascoigne () found that cultural understanding (32%), followed by business/job/career success (23%), were the most commonly cited arguments in support of language requirements by incoming freshmen not enrolled in language courses. Communication was reported as a distant fourth in importance (9%; p. 389), which is surprising given the common belief and frequent findings (e.g., Howard, Deák, & Reynolds, ; Ossipov, ) that a desire to communicate, to become fluent, brings most students to the foreign language class.…”
Section: Introductionmentioning
confidence: 82%
“…However, available research on reasons learners study languages might lead to certain speculations. Recalling Roberts's () findings, Price and Gascoigne () found that cultural understanding (32%), followed by business/job/career success (23%), were the most commonly cited arguments in support of language requirements by incoming freshmen not enrolled in language courses. Communication was reported as a distant fourth in importance (9%; p. 389), which is surprising given the common belief and frequent findings (e.g., Howard, Deák, & Reynolds, ; Ossipov, ) that a desire to communicate, to become fluent, brings most students to the foreign language class.…”
Section: Introductionmentioning
confidence: 82%
“…Learner beliefs can be focused on more external targets as well; Barcelos and Kalaja (2003) suggested that beliefs comprise students' "opinions and focusing on specifi c aspects of the language learning classroom: fi rst language (L1) usage (Rolin-Ianziti & Varshney, 2008), technology (Peters, Weinberg, & Sarma, 2009), the native versus nonnative class instructor (Hertel & Sunderman, 2009), and, in the context of incoming freshmen in a university program, preferred classroom activities (Mandell, 2002). Similarly, Price and Gascoigne (2006) sought to describe more general attitudes from college students about the "importance of foreign language study" and "postsecondary foreign language requirements" (Price & Gascoigne, 2006, p. 386). Usually, these studies have been interpretive in nature, depending on the analysis of essays, interviews, and other forms of data, but some, notably Peters et al (2009), have used surveys with Likertscale and rank-order questions to ascertain student perceptions.…”
Section: Foundations and Defi Nitionsmentioning
confidence: 99%
“…More recently, Price and Gascoigne (2006) conducted a survey on American college students' perceptions and beliefs concerning foreign language requirements. With 57% of the respondents indicating a positive attitude regarding the requirement, Price and Gascoigne considered the results quite encouraging.…”
Section: Requirement Motivationmentioning
confidence: 99%